Significance of maternal hemogram parameters as new inflammatory markers for prediction of threatened preterm labor and preterm premature rupture of membranes - Rani, Anupam; Karya, Urmila; Nehra, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Non-invasive, inexpensive and easily available simple markers are needed for timely prediction of preterm labor and preterm premature rupture of membranes (PPROM) in women at risk. Aims and objectives of current study was to study the significance of maternal hemogram parameters i.e., NLR, PLR, MPV, PDW and plateletcrit in TPL, PPROM. Methods: A total number of 150 pregnant women, 50 with PPROM (group 1), 50 with TPL (group 2) and 50 gestation matched healthy controls (group 3) attending antenatal clinic and labor room in SVBP Hospital and associated LLRM Medical College, Meerut were recruited in study. Complete blood count was done from blood sample collected in EDTA vials using 5-part automated cell analyzer device. Hematological parameters like NLR, PLR, MPV, PDW and plateletcrit were measured from CBC. Results: Patients with PPROM had increased NLR, PLR, MPV, PWD and plateletcrit than patients with threatened preterm labor group and healthy control group. Conclusions: NLR, PLR, MPV, PDW, and Plateletcrit were significantly increased in both PPROM group and TPL group compared to healthy control group and have a predictive value in PPROM and TPL. Monitoring of these parameters can be promising and cost-effective methods in prediction of TPL and PPROM.